Internet of Things(IoT) digital forensic investigation model: Top-down forensic approach methodology - Sundresan Perumal; Md Norwawi N.; Raman V. (Institute of Electrical and Electronics Engineers Inc., 2024)
Indexed by WOS/ Scopus